Womens’ Career Progression in an Australian Regional University - White, Kate; Goriss-Hunter, Anitra (Frontiers in Sociology, 2021)
This article examines the link between terms of employment (fulltime, part-time and casual) at an Australian regional university and women’s career progression. While the literature identifies lack of transparency in recruitment, promotion and retention; mobility and location; and management perceptions of women’s choice to work flexibly as factors impacting on career progression, there is little research on women’s careers in the growing Australian regional university sector. Feminist institutionalism is used to analyse how informal institutional practices resist both national legislation and institutional policies in relation to women’s career progression. Just weeks before the COVID-19 pandemic forced universities to online delivery, twenty-one women provided written responses to questions on the link between terms of employment and career progression. The study found that some senior managers endorsed a linear male career model and did not support requests for flexible work options, while also marginalising casual employees. Hence women could be dissuaded from requesting fractional appointments or job sharing that might enable them to combine work and caring responsibilities. This practice was inconsistent with both the university’s obligations under national legislation that enable employees with responsibility for the care of a child to negotiate flexible work arrangements and implementation of its institutional gender equality policies. Thus, women were often consigned to the margins, as though the legislation, policies and practices designed to promote their careers did not apply to them.